Modulation and Modeling of Three‐Dimensional Nanowire Assemblies Targeting Gas Sensors with High Response and Reliability (Adv. Funct. Mater. 10/2022). (2nd March 2022) - Han, Hyeuk Jin; Lee, Gyu Rac; Han, Yujin; Jang, Hanhwi; Cho, Eugene N.; Kim, Sunho; Kim, Chang Sub; Yim, Soonmin; Jeong, Jae Won; Kim, Jong Min; Yu, Seunghee; Tuller, Harry L.; et al.
Abstract : Gas Sensors In article number 2108891, Harry L. Tuller, Yeon Sik Jung, and co‐workers systematically engineer 3D metal oxide nanowire assemblies to achieve superior gas response, conductance, and signal stability compared to random nanowire aggregates. The 3D geometric variations and their modeling provide important insights into the electrical conduction and electrochemical responses of the assemblies, revealing the critical role of wire‐to‐wire junction points and their arrangement.